Nghiên cứu ảnh hưởng của dầu ve đến tính chất mỡ phân hủy sinh học gốc xà phòng liti trên cơ sở hỗn hợp dầu sở-ve - Hà, Phạm Thúy; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2014)
With the purpose to develop an environmental friendly biodegradable lithium grease based on non-modified vegetable oils (blend of castor oil and therasunquli oil) the paper presented the results of research for the influences of quantity of castor oil in the blend on the properties of the performed grease. The paper also emphasized these influences on the neutralization procedure in preparation of the grease.Keywords: biodegradable grease, vegetable oil based lubricant.